Cutlassfishes of the genus Lepidopus (Trichiuridae), with two new eastern Pacific species - Rosenblatt, R.H. (University of California, San Diego (USA). Scripps Inst. of Oceanography); Wilson, R.R. Jr (Gyoruigaku zasshi, 1987)
Three of the five known species of Lepidopus occur in the eastern Pacific. Lepidopus manis sp.nov. is described from a single specimen from the Galapagos Islands. The holotype of L. xantusi Goode et Bean, 1895, supposedly from Cape San Lucas, Lower California, is shown to be conspecific with L. caudatus (Euphrasen, 1788). The species heretofore reported under the name L. xantusi is described, and named L. fitchi sp.nov. It ranges from Oregon to the Gulf of California and occurs disjunctly in southern Ecuador and northern Peru. A key to the described species of Lepidopus is given and certain morphological features of L. caudatus are described. Geographic variability of L. caudatus and L. fitchi is discussed.